Targeting the Microenvironment in Esophageal Cancer - Wang, Lei; Han, Huiqiong; Wang, Zehua; Shi, Litong; Yang, Mei; Qin, Yanru (Frontiers in Cell and Developmental Biology, 2021)
Esophageal cancer (EC) is the eighth most common type of cancer worldwide and ranks sixth among the causes of cancer‑related mortality. Radical surgery is the only curative method currently available for the treatment of EC. However, as the early symptoms of EC are not evident, the majority of patients are already at an advanced stage at the time of diagnosis. Due to the high mortality rate and poor treatment efficacy for EC, millions of individuals succumb to this disease. Thus, the identification of novel treatment targets is of utmost importance and urgency. The concept of tumor microenvironment (TME) has attracted more and more attention since it was proposed. Recent studies have shown that TME is an important therapeutic target for EC. Microenvironment-targeting therapies such as immunotherapy and antiangiogenic therapy have played an indispensable role in prolonging the survival and improving the prognosis of patients with EC. In addition, many new drugs and new therapies that have been developed to target microenvironment may become our new treatment options in the future. In this review, we summarize the microenvironment of EC and the latest advances in microenvironment targeting therapy.